Perancangan Turbin Sumbu Horizontal dan Sumbu Vertikal untuk Pembangkit Listrik Tenaga Angin (Studi Kasus di Kota Bengkulu) - Anizar Indriani; Gordon Manurung; Novalio Daratha; Hendra Hendra (Universitas Bengkulu, 2019)
ABSTRACTWind Power Plant is a power plant that uses wind as an energy resources to produce electrical energy. The Bengkulu region which is mostly a coastal area with conditions of strong wind speeds that can be utilized as a source of wind power generation. Wind energy can be utilized as an alternative and renewable energy source using wind turbine. Wind turbine performance depends on the shape, position and dimensions of the turbine, etc. In this study focus on the design of wind power plants with horizontal axis turbine position and vertical axis turbine position. Wind turbine was designed with 3 blades made of wood materials. The permanent magnet DC generator are used for generator in the horizontal axis and vertical axis wind turbine positions with maximum power that can be generated at 800 Watt. Testing of the two types of turbines was carried out on the coast of Bengkulu city. The results shows that the horizontal axis wind power plant design starts rotating at a wind speed of 3.5 m / s, while the vertical axis wind power plant design starts rotating at a wind speed of 6.5 m / s. The voltage generated by the horizontal axis wind power plant at a wind speed of 3.5 m / s is 12 Volts. The voltage generated by the vertical axis wind power plant at a wind speed of 6.5 m / s is 9 Volts.